Bahasa Inggris: Bahasa Inggris - ramadhaniharahap, laylasuciramadhaniharahap12 (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The purpose of this study was to determine whether there is a correlation between students' vocabulary mastery and reading comprehension at SMK Bina Profesi Pekanbaru. The population of this study was a total population of 128 students. The sample was taken using a simple random sampling process. This study employed quantitative methodologies. Through the utilization of Vocabulary Test and Reading Comprehension Test. The study employed the Pearson product-moment coefficient calculation in SPSS to evaluate the correlation between students' vocabulary mastery and reading comprehension. The analysis results show that there is significant correlation between vocabulary mastery and reading comprehension. This can be seen from the significance value of the data which is 0.001 < 0.05. The Pearson correlation value is 0.563, which indicatels that thel lelvell olf colrrellatioln is grelatelr and thel direlctioln is polsitivel, which means H0 is rejected and the researcher assumption (Ha) is accepted. It can be concluded that the significant relationship between Vocabulary Mastery and Reading Comprehesion.